Development and testing of a power operated coconut oil expeller - AMRETHA KRISHNAN A.K MANSHOOBA P.M SA-ADA ABDURAHIMAN SAROOP C.L; Dr. Jayan P.R (Guide) (Tavanur 2016 DEPARTMENT OF FARM POWER MACHINERY AND ENERGY)
Development and testing of a power operated coconut oil expeller
Development and testing of a power operated coconut oil expeller